117k views
4 votes
Factor 5(2x+7)+4(2x+7)
enter your answer in the box​

2 Answers

7 votes

Answer:


63 + 18x

Explanation:


5(2x + 7) + 4(2x + 7) \\ \\ (10x + 35) + (8x + 28) = 18x + 63

* The above answer is written in reverse, which is the exact same result.

I am joyous to assist you anytime.

User CedricB
by
5.7k points
3 votes

Answer:

18x+63

Explanation:

First you've to simplfy it, multiply the first bracket by 5 and the second by 4.

= (5)(2x)+(5)(7) + (4)(2x)+(4)(7)

= 10x+35+8x+28

Combine Like Terms:

= 10x+35+8x+28

= (10x+8x)+(35+28)

= 18x+63

User Ishara Meegahawala
by
5.3k points